MSME Training and Community Empowerment Through Human Resource Quality Improvement - Dika Prawita; Bernadetta Maharani; Epsilandri Sepyarini (IMPACTS: International Journal of Empowerment and Community Services, 2025)
This community service activity aims to provide training to the community, covering aspects of digital marketing, branding, and human resource management. This activity is part of the Real Work Lecture (KKN) program, which focuses on community empowerment through improving the quality of human resources. Although Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy, they still face challenges such as limited marketing and technological adaptation. Therefore, HR empowerment is seen as the key to success. The method used is descriptive qualitative through field observation, interviews, and documentation. The results show that the use of technology, especially digital marketing and product branding, is an effective solution to overcome these challenges and expand market reach. The training provided by Mr. Dika Prawita, S.E., M.M. and Mrs. Bernadetta Diansepti Maharani, S.E., M.M. is expected to increase the capabilities and motivation of the community to develop their businesses